ANALISIS HARGA SAHAM PADA PT. GARUDA INDONESIA TBK TAHUN 2020-2021 - Aprialinita, Dhea; Djahmur, Fitria; Nurliyana, Nurliyana; Yusrizal, Yusrizal (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
The share price is the price set by the company for other parties who wish to have share ownership rights. Price Earning Ratio is a ratio to measure the success of management in achieving profits for shareholders. PER value <10 is cheap, >10 is expensive, but if it is negative it means the company is at a loss. Based on the results of the discussions that have been described, it is certain that PT Garuda Indonesia suffered losses from the first quarter of 2020 to the third quarter of 2021, which of PT Garuda Indonesia's PER value experienced a minus, even Garuda Indonesia's PER value touched -22,361 in the first quarter of 2021. From the results of the study, it can be said that PER is quite influential on stock prices but does not measure investors in assessing Garuda's stock prices.